2001
DOI: 10.1136/heart.86.4.411
|View full text |Cite
|
Sign up to set email alerts
|

Does cytosine-thymine-guanine (CTG) expansion size predict cardiac events and electrocardiographic progression in myotonic dystrophy?

Abstract: Objective-To assess whether the size of the cytosine-thymine-guanine (CTG) expansion mutation in myotonic dystrophy predicts progression of conduction system disease and cardiac events. Design-Longitudinal study involving ECG and clinical follow up over (mean (SD)) 4.8 (1.8) and 6.2 (1.9) years, respectively, of patients stratified by CTG expansion size (E0 to E4). Patients-73 adult patients under annual review in a regional myotonic dystrophy clinic. Patients were grouped into E0/E1 (n = 25), E2 (n = 34), and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(49 citation statements)
references
References 27 publications
1
48
0
Order By: Relevance
“…Although such a correlation between the extent of CTG repeats and the degree of cardiac involvement has been described in some series, others have shown conflicting results (9,17,18,25,(34)(35)(36)(37)(38)(39). Of note is the study by Lazarus et al (17); using precise invasive electrophysiological measurements, the study was unable to show such a relationship between conduction delays and the extent of CTG repeats.…”
Section: Discussionmentioning
confidence: 96%
“…Although such a correlation between the extent of CTG repeats and the degree of cardiac involvement has been described in some series, others have shown conflicting results (9,17,18,25,(34)(35)(36)(37)(38)(39). Of note is the study by Lazarus et al (17); using precise invasive electrophysiological measurements, the study was unable to show such a relationship between conduction delays and the extent of CTG repeats.…”
Section: Discussionmentioning
confidence: 96%
“…Eleven follow up studies (n = 1365) reported data on the incidence of SCD in MD1-patients [4,10,[13][14][15][18][19][20][21][22][23]. The studies reported 70 SCDs during a total of 12414 follow up years.…”
Section: Sudden Cardiac Deathmentioning
confidence: 96%
“…This causes the multisystemic affections of the disease: Myotonia, muscular dystrophy with primarily distal and facial muscle weakness and wasting, cataracts, cardiac involvement, hypogonadism, hypersomnia, cognitive impairment, and frontal balding [1,3] with symptoms ranging from very mild (cataracts at middle age) to very severe (neonatal lethal hypotonia and death) [4]. The size of the CTG expansion has been reported to correlate with disease severity and age of onset [5], intellectual impairment [6], cardiac involvement [7,8], impaired cardiac and brain glucose metabolism [9], radiologic pharyngoesophageal alterations [10], and muscle strength [11]. Furthermore, a study in a small cohort has shown a correlation between the degree of abnormal calcium metabolism and number of CTG repeats [12].…”
Section: Introductionmentioning
confidence: 98%